2015
DOI: 10.1111/tct.12348
|View full text |Cite
|
Sign up to set email alerts
|

Workplace formative assessment: faculty members’ beliefs

Abstract: WFA has been shown to stimulate learning through the exchange of feedback with a learner about gaps in his or her practice. This study showed that WFA is not yet used in the majority of dermatology training programmes. Time for faculty members to perform WFA was the most cited barrier to the use of WFA, but few studies have investigated the actual time requirement. Secondly, faculty members' interest may be encouraged through training and an increased awareness of the impact of WFA. For example, the evidence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Second, studies have shown that supervisors' initiation of DO may conflict with trainees' pursuit of independence and autonomy (being core values in medicine), emphasizing the role of sociocultural factors in clinical education [17,18]. Third, supervisors may feel that trainees alter their behaviour during the observation, thereby raising concerns that DOs assess the 'shows how' level rather than what trainees actually 'do' in clinical practice [19,20]. Finally, recent research has suggested that supervisors may perceive low selfefficacy in performing observations of clinical performance and the provision of feedback [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Second, studies have shown that supervisors' initiation of DO may conflict with trainees' pursuit of independence and autonomy (being core values in medicine), emphasizing the role of sociocultural factors in clinical education [17,18]. Third, supervisors may feel that trainees alter their behaviour during the observation, thereby raising concerns that DOs assess the 'shows how' level rather than what trainees actually 'do' in clinical practice [19,20]. Finally, recent research has suggested that supervisors may perceive low selfefficacy in performing observations of clinical performance and the provision of feedback [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Second, studies have shown that supervisors' initiation of DO may conflict with trainees' pursuit of independence and autonomy (being core values in medicine), emphasizing the role of socio-cultural factors in clinical education (17,18). Third, supervisors may feel that trainees alter their behaviour during the observation, thereby raising concerns that DOs assess the 'shows how' level rather than what trainees actually 'do' in clinical practice (19,20). Finally, recent research has suggested that supervisors may perceive low self-efficacy in performing observations of clinical performance and the provision of feedback (19,21).…”
Section: Introductionmentioning
confidence: 99%
“…Third, supervisors may feel that trainees alter their behaviour during the observation, thereby raising concerns that DOs assess the 'shows how' level rather than what trainees actually 'do' in clinical practice (19,20). Finally, recent research has suggested that supervisors may perceive low self-efficacy in performing observations of clinical performance and the provision of feedback (19,21).…”
Section: Introductionmentioning
confidence: 99%
“…Second, studies have shown that supervisors' initiation of DO may conflict with trainees' pursuit of independence and autonomy (being core values in medicine), emphasizing the role of socio-cultural factors in clinical education (16,17). Third, supervisors may feel that trainees alter their behaviour during the observation, thereby raising concerns that DOs assess the 'shows how' level rather than what trainees actually 'do' in clinical practice (18,19). Finally, recent research has suggested that supervisors may perceive low self-efficacy in performing observations of clinical performance and the provision of feedback (18,20).…”
Section: Introductionmentioning
confidence: 99%
“…Third, supervisors may feel that trainees alter their behaviour during the observation, thereby raising concerns that DOs assess the 'shows how' level rather than what trainees actually 'do' in clinical practice (18,19). Finally, recent research has suggested that supervisors may perceive low self-efficacy in performing observations of clinical performance and the provision of feedback (18,20).…”
Section: Introductionmentioning
confidence: 99%